Conceptualization of Legal Protection of Registered Trademark Rights in Realizing Just Legal Certainty - Ghuffran, Mohammad (Formosa Journal of Science and Technology, 2024)
Article 21 paragraph (1) letters b and c and Article 21 paragraph (3) of Law Number 20 of 2016 concerning Trademarks and Geographical Indications provide protection and regulations for well-known brands in Indonesia. According to Article 21 paragraph (1) letter b of the MIG Law, if a brand is conceptually or completely identical to a well-known brand that belongs to another party for products and/or the like, DJHKI must reject the application. According to the explanation of Article 21 paragraph (1) letter b of Law Number 20 of 2016 concerning Geographical Indications, a brand's popularity must be assessed by taking into account the public's general awareness of the brand in the relevant industry as well as its reputation as a well-known brand that has been earned through extensive marketing campaigns, owner investments in multiple countries, and documentation of the brand's registration in multiple countries. If the aforementioned factors are deemed insufficient, the Commercial Court may mandate that an impartial organization carry out a study in order to reach a determination on the level of popularity of the brand that serves as the foundation for the denial. Furthermore, as long as they fulfill specific standards that will be further outlined by government regulation, commodities and/or services that are not of the same kind may also be covered by Article 21 paragraph (1) letter c. Furthermore, paragraph (3) of Article 21 clarifies that a brand cannot be registered based on an application filed by a party acting dishonestly.